Bibliometric Analysis of Research Trends and Novelties for Pneumonia in Children - Ariyani Lutfitasari; Fitriani Nur Damayanti; Budi Santosa; Lia Mulyanti; Umi Khasanah (Jurnal Keperawatan Indonesia, 2024)
Pneumonia is the leading cause of death among children globally, with most cases occurring in low- and middle-income nations. Pneumonia in children has been thoroughly researched in numerous countries throughout the world. However, no research performed bibliometric analyses of pneumonia in children. This study aims to use a biometric analysis to determine trends in the number of publications, the number of citations, network visualization, overlay visualization, and density visualization concerning the issue of pneumonia in children. This research method employs a systematic review with stages adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. The highest publication increase occurred in 2020, with a rise of 2,739. The number of citations increases exponentially from year to year. The most cited article is "The Epidemiology and Pathogenesis of Coronavirus Disease (COVID-19) Outbreak," with 3,680 citations. Keywords and interest trends in pneumonia in children focus on viral pneumonia. The endeavor to perform a bibliometric analysis of pneumonia in children may be revisited in the next few years. Notably, this article only extracts data from scientific articles within the app.dimension.ai database. Further research may be conducted to add other databases and ensure a more comprehensive understanding of pneumonia in children. Keywords: bibliometric analysis, children, novelty, pneumonia, risk factor, trend   Abstrak Analisis Bibliometrik Tren dan Kebaharuan Penelitian terkait Pneumonia pada Anak. Pneumonia adalah penyebab utama kematian di antara anak-anak di seluruh dunia, dengan sebagian besar kasus terjadi di negara-negara berpenghasilan rendah dan menengah. Pneumonia pada anak telah diteliti secara menyeluruh di berbagai negara di seluruh dunia. Namun, belum ada penelitian yang melakukan analisis bibliometrik terhadap pneumonia pada anak-anak. Penelitian ini menggunakan analisis bibliometrik untuk menentukan tren jumlah publikasi, jumlah kutipan, visualisasi jaringan, overlay visualization, dan visualisasi densitas terkait masalah pneumonia pada anak. Metode penelitian ini menggunakan tinjauan sistematis dengan tahapan yang mengikuti Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Peningkatan publikasi tertinggi terjadi pada tahun 2020, dengan peningkatan sebesar 2.739. Jumlah kutipan meningkat secara eksponensial dari tahun ke tahun. Artikel yang paling banyak dikutip adalah “Epidemiologi dan Patogenesis Wabah Coronavirus Disease (COVID-19),” dengan 3.680 kutipan. Kata kunci dan tren minat terhadap pneumonia pada anak berfokus pada pneumonia virus. Upaya untuk melakukan analisis bibliometrik pneumonia pada anak mungkin akan ditinjau kembali dalam beberapa tahun ke depan. Sebagai catatan, artikel ini hanya mengekstrak data dari artikel ilmiah dalam database app.dimension.ai. Penelitian lebih lanjut dapat dilakukan untuk menambahkan database lain dan memastikan pemahaman yang lebih komprehensif tentang pneumonia pada anak-anak. Kata Kunci: anak-anak, analisis bibliometrik, faktor risiko, kebaharuan, pneumonia, tren